Observation of the rare decay B0→K0SK±π∓ - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We report an analysis of charmless hadronic decays of neutral B mesons to the final state K0SK±π∓, using a data sample of (465±5)×106 B¯¯¯B events collected with the BABAR detector at the Υ(4S) resonance. We observe an excess of signal events with a significance of 5.2 standard deviations including systematic uncertainties and measure the branching fraction to be B(B0→K0SK±π∓)=(3.2±0.5±0.3)×10−6, where the uncertainties are statistical and systematic, respectively.